Modelling the Relationship between Final Energy Consumption, Share of Energy From Renewable Sources and Greenhouse Gases in the EU and Romania - GEORGE-CORNEL DUMITRESCU (Global Economic Observer)
The EU has to reduce greenhouse gas emissions by 55% compared to the levels recorded in 1990 by 2030, despite the higher level of ambition suggested by the European Parliament, namely 60%. It is a very optimistic goal considering the different levels of compliance to the intermediary targets by the EU member states. Reducing energy consumption or increasing the share of green energy seems to be the directions to follow to meet the requirements set by the Commission; energy consumption is the highest generator of such gases that are detrimental to all life forms and the planet. In our paper, we are modelling the relationship between final energy consumption, greenhouse gas emissions and the share of energy from renewable sources in the EU and Romania to assess their statistical significance in order to identify how the energy sector could turn into a lever in the transition towards the green economy. We identify a strong statistically significant relationship between final energy consumption and greenhouse gas emissions in the EU27, as opposed to Romania`s case, in which the correlation coefficient is extremely weak. We also find out that the correlation between the share of energy from renewable sources and greenhouse gas emissions is stronger and more statistically significant in Romania than in the EU27, explaining somehow the first findings. For our analysis, we use the database of Eurostat and several statistical tools.